Increased risks of epilepsy and neuropsychiatric diseases in children of mothers with alcoholic liver disease. (11th December 2012) - Stokkeland, Knut; Ebrahim, Fereshte; Hultcrantz, Rolf; Ekbom, Anders
Abstract Background Pregnancy in women with liver disease may increase the risk of fetal complication. Data on disease frequencies in children born to mothers with alcoholic liver disease do not exist, although we do know that prenatal alcohol exposure may affect the fetus negatively. Aims The aim of this study was to assess the relative risk of neuropsychiatric diseases in children who were born to mothers with chronic liver diseases. Methods We linked the Hospital Discharge Register, Medical Birth Register and Pharmaceutical Register in Sweden between 1969 and 2009 to identify women with liver disease. We identified their children, up to the age of 16 in the Medical Birth Register, born between 1973 and 2009. Between 2005 and 2009, we identified every prescription that was dispensed to these children. Results We identified 5 124 children of mothers with alcoholic liver disease. There were 22 960 children of mothers with non‐alcoholic liver disease. For controls, we used 10 sex‐, age‐ and birthplace‐matched children. There were more children born to mothers with alcoholic liver disease before the birth who had been dispensed antiepileptics (n = 11, RR = 3.2 (1.6–6.4)), neuroleptics (n = 7, RR = 5.0 (2.0–12.5)) and drugs to treat attention deficit hyperactivity disorders (n = 22, RR = 5.9 (3.7–9.4)) compared with sex‐, age‐ and regionally adjusted controls. Children born to mothers with non‐alcoholic liver disease had significantly increased risk of being dispensed drugs to treat attention deficit disorders (RR = 2.2 (1.8–2.6)). Conclusions Mothers with alcoholic liver disease have increased risks of having children with severe neurological and psychiatric disorders.